Fractional Flow Reserve following Percutaneous Coronary Intervention. (5th June 2020) - Thakur, Udit; Khav, Nancy; Comella, Andrea; Michail, Michael; Ihdayhid, Abdul R.; Poon, Eric; Nicholls, Stephen J.; Ko, Brian; Brown, Adam J.
Abstract : Fractional flow reserve (FFR) is routinely used to determine lesion severity prior to percutaneous coronary intervention (PCI). However, there is an increasing recognition that FFR may also be useful following PCI to identify mechanisms leading to restenosis and the need for repeat revascularization. Post-PCI FFR is associated with the presence and severity of stent under-expansion and may help identify peri-stent-related complications. FFR pullback may also unmask other functionally significant lesions within the target vessel that were not appreciable on angiography. Recent studies have confirmed the prognostic utility of performing routine post-PCI FFR and suggest possible interventional targets that would improve stent durability. In this review, we detail the theoretical basis underlying post-PCI FFR, provide practical tips to facilitate measurement, and discuss the growing evidence supporting its use.